Optimalisasi Penerapan PSAK 109 dalam Meningkatkan Transparansi dan Akuntabilitas Laporan Keuangan Lembaga Sosial Islam - Afriani, Ekha; Nabila; Masyhuri (Yayasan Darussalam Patalassang, 2025)
This study aims to analyze the role and challenges of implementing PSAK 109 on Zakat, Infak, and Sedekah and ISAK 35 on Waqf in the financial reporting of Islamic social institutions. This study uses a descriptive qualitative approach with a literature study method and documentation of regulations, financial reports, and relevant previous research results. This result show the implementation or application of these standards in various financial and non-financial institutions has not been running optimally. This can be caused by several factors, such as a lack of understanding of these standards, limited human resources who are competent in the field of sharia accounting, minimal training or socialization, and the absence of strict supervision of the implementation of these standards. As a result, the main objective of preparing these standards has not been fully achieved in the field. The findings show that the main obstacles come from limited human resources, minimal understanding of sharia standards, and lack of support for financial reporting technology. This gap risks reducing the quality of information conveyed to the public. Therefore, a strategy is needed to optimize the implementation of these standards so that Islamic social fund management institutions are able to meet regulatory aspects while building public trust professionally and with integrity. This study contributes to encouraging the improvement of the quality of sharia-based financial governance in Indonesia.